Penumbuhan Karakter Sosial Santri di Pondok Pesantren - Dora, Riza; Arif, Muhamad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Islamic boarding schools are institutions that grow and develop within the indigenous culture of the archipelago and are believed to have become the main foundation in developing Islamic treasures as well as science and human morals. Islamic boarding schools have consistently produced a generation that can respond to the challenges and dynamics of the times, especially in the context of Islamic-based education. Character education in Islamic boarding schools is mostly delivered through the typical methods and approaches inherent in this institution. Therefore, the formation of social character in Islamic boarding schools must leave a deep imprint on the students, so that it has an influence when they socialize and socialize. One of the main methods in this case is through example. The problems to be answered through this research include: 1) How do Islamic boarding schools foster social character? 2) What are the supporting and inhibiting factors in the development of social character? Data collection methods in this research include observation, interviews, and documentation. The results of the study show that the formation of the social character of students at the Nurul Ulum Salafiyah Islamic Boarding School is carried out through various methods, such as the example of the ustadz, curriculum implementation, and Islamic boarding school programs.